April D. DeConick, The Gnostic New Age: How a Countercultural Spirituality Revolutionized Religion from Antiquity to Today. (26th January 2023) - Huff, Peter A
Abstract : April D. DeConick, The Gnostic New Age: How a Countercultural Spirituality Revolutionized Religion from Antiquity to Today (New York: Columbia University Press, 2016), 380 pp., 37.00 (cloth), 28.00 (paperback).